Military procurement, industry structure and regional conflict - Paul Dunne; María del Carmen García-Alonso; Paul Levine; Ron Smith (University of Kent, Department of Economics, 2005)
In this paper, we construct a model of market structure in the global arms industry linking concentration, military procurement, international trade and regional conflict. We show how concentration depends on the willingness of producers to import for their military needs and on the relative size of the external market of non-producers. We show that there can be substantial gains to producers from cooperation in the procurement process, but also small gains to non-producers involved in regional arms races. Arms export controls that limit the level of technology that can be exported to non-producers distribute these cooperative gains from producers to non-producers.
Keywords: F12; H56; L10; 330; military procurement; market structure; arms trade; arms races; Rüstungsindustrie; Rüstungsgut; Marktstruktur; Militärische Beschaffung; Verteidigungsökonomik